Surgical Management of Neurotuberculosis: Review of Radiological Spectrum - Gautam, V K S; Singh, Ravinder (International Journal of Health, 2013)
Paper reviews the radiological findings of 31 patients of central nervous system tuberculosis (CNS TB) undergone the neurosurgical intervention. As the diagnosis of CNS TB poses a difficulty due to non specific clinical presentation, inability to retrieve microorganism or histopathological tissues, radiological investigations are useful in assessment, diagnosis and treatment of CNS TB. This review may serve as guide to clinicians for a practical approach in investigating cases of neurotuberculosis.